Komunikasi Interpersonal Pengasuh Dalam Pembinaan Akhlak Pada Anak Asuh di Panti Sosial Asuhan Anak Putra Utama 3 - Fatimah Al Salamah; Muhammad N. Abdurrazaq; Achmad Abrory Arief (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The phenomenon of moral or moral decadence is often seen by a wide audience today, starting from violence, brawls, exclusivism, to the loss of respect for foster children towards teachers/caregivers. All forms of dysfunction are indicated because good interpersonal communication has not been established. This research aims to analyze the interpersonal communication developed by caregivers at the Putra Utama 3 Children's Orphanage in fostering noble morals, as well as the efforts carried out and the obstacles faced during the implementation of moral guidance. Researchers used a qualitative approach with a field study type of research involving orphanage caregivers and several foster children as research informants. Data collection uses three approaches, namely observation, interviews and documentation. Meanwhile, data analysis uses three models, namely data reduction, data exposure, and drawing conclusions. The results of the research concluded that interpersonal communication among caregivers at the Putra Utama 3 Children's Social Home is something that is fundamentally implemented and represents all forms of action carried out through moral development. This is realized by social care caregivers through moral development efforts, both verbal and nonverbal. So, the obstacles faced during moral development can be resolved well.